OWE-020 Survival and CT defined sarcopenia in patients with intestinal failure on HPN. (8th June 2018) - Oke, SM; Rye, B; Malietzis, G; Baldwin, R; Bottle, RA; Gabe, SM; Lung, PFC
Abstract : Introduction: Sarcopenia is recognised in patients with intestinal failure (IF) and has been associated with poorer survival in several chronic diseases. CT can measure sarcopenia through a L3 skeletal muscle index (LSMI). We aim to evaluate the prevalence of sarcopenia in our IF population using LSMI, and evaluate the effect of home parenteral support (HPN) on LSMI and survival. Additionally, we aim to assess any association between LSMI, BMI and other anthropometric measurements. Methods: IF patients on HPN treated at St Mark's Hospital between 1/1/2006–1/10/2016 were identified from a prospectively maintained database. Patients were included if they were on HPN and had 2 CTs: the first ≤30 days before start of HPN (pre-HPN); the second ≥100 days from HPN start (post-HPN). Patient records were reviewed to obtain clinical and demographic information and date of death. Anthropometric measurements and BMI contemporaneous to CT scans were recorded. Results: 64 patients met inclusion criteria (M:F 1:1). 83% of our cohort had LSMI below previously published thresholds for sarcopenia. Mean pre-HPN LSMI was 36.5±6.8 cm 2 /m 2 . Mean BMI pre-HPN was 22.1±4.8 kg/m 2 . Both BMI (p<0.001) and LSMI (p=0.003) increased post-HPN. A positive correlation was seen between BMI and LSMI pre (p<0.001) and post-HPN (p=0.003). No correlation was seen between LSMI and anthropometric measurements pre-HPN (p=0.78) or post-HPN (p=0.96). 11 (17%) patients died during the study period; a low LSMI pre-HPN was not a risk factor for mortality (HR 0.97 p=0.55). Conclusions: This study is the first to look at sarcopenia and survival using CT defined LSMI in the IF population. 83% of our cohort had a pre-HPN LSMI below previously published thresholds, yet we found no relationship between lower baseline LSMI and survival. This may reflect the heterogeneity of the prognoses of the IF population, or that parenteral nutrition itself affects survival. Our study showed that LSMI and BMI improved following HPN but demonstrated that other anthropometric measurements had poor correlation with LSMI and showed no significant improvement overall after HPN, confirming the known problems of inter-operator and patient variability of these measurements. Whilst we found significant correlation between LSMI and BMI, BMI significantly underestimated the presence and degree of sarcopenia. We have shown LSMI can provide an objective and reproducible measure of sarcopenia in IF. Future larger studies should be performed to evaluate associations with patient outcomes and utility in clinical decision making.